Paul’s Metaphor of Death: Death as Salvation - Kim, Seo-Jun ca. 20./21. Jahrhundert (The expository times, 2025)
This study examines the meaning behind Paul’s metaphorical statements about death and explores the powerful and positive challenges they present. Paul uses the language of death in various contexts, with a range of meanings. Among them, several recurring phrases stand out in his letters such as the death of all people (2 Cor 5:14-15), death to the law (Gal 2:19-20), death to sin and desire (Gal 5:24), death to the world (Gal 6:14), death to sin (Rom 6:2), and death of the old self or body of sin (Rom 6:3-6). These expressions describe a deep inner transformation that occurs through faith and the work of the Holy Spirit. In Paul’s view, this kind of death is not the end but points to salvation; it marks the beginning of a new life. It represents death that goes beyond the physical and even overcomes the fear of final judgment. For Christians living between this inner transformation and their eventual physical death, Paul’s language gives new meaning to their lives and how they relate to the world.